Assessing Racial/Ethnic and Gender Gaps in Political Science PhD Students' Methodological Self-Efficacy. Issue 1 (4th January 2022) - Smith, Amy Erica; Gillooly, Shauna N.; Hardt, Heidi
ABSTRACT: Most research on diversity within political methodology focuses on gender while overlooking racial and ethnic gaps. Our study investigates how race/ethnicity and gender relate to political science PhD students' methodological self-efficacy, as well as their general academic self-efficacy. By analyzing a survey of 300 students from the top 50 US-based political science PhD programs, we find that race and ethnicity correlate with quantitative self-efficacy: students identifying as Black/African American and as Middle Eastern/North African express lower confidence in their abilities than white students. These gaps persist after accounting for heterogeneity among PhD programs, professional and socioeconomic status, and preferred methodological approach. However, small bivariate gender gaps disappear in multivariate analysis. Furthermore, gaps in quantitative self-efficacy may explain racial/ethnic disparities in students' broader academic self-efficacy. We argue that the documented patterns likely lead to continued underrepresentation of marginalized groups in the political methodology student body and professoriate.